Dvojí svět Puzova Kmotra - Marek, Jakub (Lidé města, 2007)
In 2006 and 2007, the Philosophy Module of the Faculty of Humanities at the Charles University organized two literary-philosophical symposia in Lipnice nad Sázavou. Topic of the first symposium (June 21, 2006) was Jaroslav Hašek’s novel “Good Soldier Švejk”; the central topic was war as a certain important form of existential condition of human beings in the world. The symposium has resulted in an anthology containing contributions “Hašek and War. War as epochal human openness towards the world” (published in 2007, 105 pages). The anthology contains contributions by Ladislav Benyovszky, Jakub Češka, Richard Hašek, Josef Kružík, Jakub Marek, Aleš Novák, Jaroslav Novotný, and Richard Zika. The topic of the second symposium (June 26, 2007) was the novel “The Godfather” by Mario Puzo and its film trilogy adaptation directed by F. Coppola. The core of the symposium was five contributions by Peter Brezina, Jakub Češka, Jakub Marek, Jaroslav Novotný, and Stanislav Synek. To sum up, we might say that the contributions and subsequent discussions showed that, at the first sight the deliberately antimodernistic and to certain extent utopian Puzo’s novel presents inner perversity of the depicted alternative world of a “family”. Apart from these contributions, I consider the short but dense comment by Ladislav Benyovszky to be important. It refers to a uniform context (“die Sache selbst” as cosa nostra) of disclosed types of human activities used to depict the world of “The Godfather” novel. Number of contributions of the second symposium was too small to publish a separate anthology. For that reason we present the texts of the second symposium in the magazine Urban People. In addition, there are three other articles: Taťána Ospálkova’s “The Godfather – Genre rules: Gangster movie or family saga?”, Jakub Marek’s “Double world of Puzo’s The Godfather”, and Jaroslav Novotný’s “Nostalgia, method and tragedy. Back to Mario Puzo’s novel The Godfather”. It is supplemented with a short reflection of these symposia the “Events at Lipnice that are hidden”, by the Jaroslav Novotný and published in Lipnice Panorama in summer of 2007.